Penyajian Laporan Keuangan Masjid Sesuai ISAK No. 35 Untuk Peningkatan Transparasi dan Akuntabilitas: (Studi Kasus Pada Masjid At- Tadzkiroh, Sidoarjo) - Ade Irma Suryani Lating (Owner : Riset dan Jurnal Akuntansi, 2023)
The mosque is a non-profit organization that is not oriented to making a profit. In carrying out its activities, the mosque obtains its capital, namely donors. Therefore, the financial statements made are required for transparency and accountability. A good financial report is in accordance with accounting financial standards, namely ISAK No. 35 as a substitute for PSAK No. 45 which is used to prepare financial reports in non-profit organizations. The purpose of this study is to find out about the Implementation of ISAK No. 35 in the Preparation of Mosque Financial Reports for the Creation of Transparency and Accountability. The type of research used is in the form of qualitative research. Data obtained by means of Observations, Interviews, and Documentation conducted at the AT-Tadzkiroh Mosque. The data obtained in the form of primary data obtained through information from several informants while secondary data in the form of reports of monthly cash receipts and disbursements. The results of the research carried out explain that the AT-Tadzkiroh mosque still has not implemented financial reports in accordance with ISAK accounting standards No. 35, the reports made are only reports of cash receipts and disbursements and total monthly balances. The mosque still has not depreciated its fixed assets. The mosque has reported its financial statements to donors, although the financial statements presented are still in a simple form